Plasma concentration of MMP-1 and MMP-2 in boys with cryptorchidism and its lack of correlation with INSL3 and inhibin B. (18th August 2019) - Matuszczak, Ewa; Komarowska, Marta Diana; Sankiewicz, Anna; Ołdak, Łukasz; Gorodkiewicz, Ewa; Debek, Wojciech; Milewski, Robert; Tylicka, Marzena; Hermanowicz, Adam
Abstract: The matrix metalloproteinases are enzymes capable of remodeling of extracellular matrix, and modulate the behavior of cells. Maturation of gubernaculum and spermatogenesis demand proper equilibrium of metalloproteinases and their inhibitors. The aim of this survey was to investigate the levels of matrix metalloproteinase type 1 (MMP-1) and matrix metalloproteinase type 2 (MMP-2) in the plasma of children with unilateral cryptorchidism along with levels of Insulin-like Peptide 3 (INSL3) and inhibin B. INSL3 have a role in gubernaculum development. Inhibin B is produced by Sertoli cells, and its levels reflect the status of the testis germinative epithelium. Fifty boys with an undescended testicle, aged 1–4 years (median = 2.4 years) were enrolled into the study. Fifty boys with inguinal hernia aged 1–4 years, served as controls (median age = 2.1 years). Investigators assessed the MMP-1 and MMP-2 concentrations using Surface Plasmon Resonance Imaging. The levels of INSL-3 and inhibin B were assessed using commercial enzyme-linked immunosorbent assay ELISA. The median concentration of MMP-1 and MMP-2 in the blood plasma of patients with unilateral cryptorchidism, was nearly 2-folds higher than in controls. The great area under the ROC curve with the cut off value of 0.865 for MMP-1, and 0.819 for MMP-2, indicates the high clinical sensitivity and specificity of the test of plasma levels of MMP-1 and MMP-2 for boys with cryptorchidism. The increased plasma levels of MMP-1 and MMP-2, probably reflect the level of apoptosis of the germ cells in undescended testicles, in response to the heat stress during the period of prepubertal testis development. In the group of cryptorchid boys, we found slightly lower concentrations of INSL3, without statistical significance and without correlation with MMP-1 and MMP-2 levels. There were no significant differences in the levels of inhibin B in the group of boys with cryptorchidism and boys with inguinal hernia and it also did not correlate with MMP-1 and MMP-2 concentrations.